“Pasangan Minimal” Fonem Dasar Pembelajaran Materi Fonologi Bahasa Indonesia - Ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Evidence as well as the goal of writing articles related to the statement: that the existence of